دراسة أثر إضافة مطحون قشور البرتقال الناتجة عن تصنيع عصير البرتقال على أهم خصائص البسكويت فضلاً عن تحسين المُنتَج بإضافة إنزيم الإكزيلينيز (Latakia University Journal -Biological Sciences Series, 2017)
يُستخدم البرتقال في تصنيع العصير، وينتج عنه كَمّيات كبيرة من المنتجات الثانوية. تمﱠ تحليل التركيب الكيميائي والمقدرة على ربط الماء من قِبل قشور البرتقال، حيث أظهرت النتائج أنَّها تحتوي على كمّيات مرتفعة من الألياف الخام والمركبات الفينولية ومضادات الأكسدة ومقدرة عالية على ربط الماء. كما أُدخلت في تحضير البسكويت من خلطات تحوي نسباً مختلفةً من مطحون قشور البرتقال (5، 10، 15، 20، 25)% ثم تقييم الخصائص الفيزيائية والحسّية والتركيب الكيميائي والخصائص الريولوجية لهذه الخلطات.لم يُظهر التقييم الحسّي أي فروقات معنوية بين الشاهد ونسبة الإضافة 10% من مطحون قشور البرتقال، أمَّا من ناحية المؤشرات الفيزيائية أي القَطْر، والسماكة ومعدَّل التمدُّد, فانخفض القَطْر والسماكة في البسكويت الحاوي عليها، بينما ارتفعت قيم معدَّل التمدُّد مع ارتفاع مستوياته المضافة.أوضحت النتائج أنَّ دمج مطحون قشور البرتقال بالبسكويت رفع نسبة الألياف الخام والرماد والمحتوى الفينولي والمقدرة المضادة للأكسدة، وقلل من الكربوهيدرات. وأظهرت الخصائص الريولوجية لخلطات الدقيق ارتفاعاً في امتصاص الماء والثباتية. خفَّضت إضافة ppm 40 من إنزيم الإكزيلينيز من قساوة العينات بشكل عام، كما خفَّضت قِيَمَ معدَّل التمدَّد مقارنة بعينة الشاهد غير المحتوية على الإنزيم. أظهرت نتائج التقييم الحسي قبولاً جيداً للبسكويت المحتوي على 10% مطحون قشور البرتقال سواءً مع استخدام إنزيم الإكزيلينيز أو بدونه.Orange is used in the juice industry, yielding important quantities of by products. Orange peel is analyzed for chemical composition and water holding capacity. Data show that, it has high amount of crude fiber, phenolic contents and antioxidant capacity, also it has high level of water holding capacity. Biscuits are prepared from blendes which contain a different proportion (5, 10, 15, 20 and 25)% of orange peel flour are also evaluate for physical and sensory characteristics, chemical composition and rheological properties for this blendes. The sensory evaluation does not show any significant difference between control and that adds with 10% of orange peel flour. Physical parameters, namely, diameter, thickness and spread ratio were tested. The diameter and thickness of orange peel substituted biscuits were decreased, whereas spread ratio of biscuits increase with increasing levels of it.The data reveals that incorporation of orange peel powder in biscuits increase crude fiber, ash, phenolic contents and antioxidant capacity, it decreases the carbohydrate content. Rheological properties of the blended flour show increase in water absorption and stability.Addition of 40ppm xylanase enzyme reduce the hardness value of the sample in general, it also decrease the spread ratio as compared to control samples with no enzyme added.Sensory evaluation results show good overall acceptability scores for the biscuits contain 10% orange peel with and without xylanase.